1990
DOI: 10.1111/j.1439-0523.1990.tb00426.x
|View full text |Cite
|
Sign up to set email alerts
|

The Inheritance of Resistance to Septoria Glume Blotch II. The Wild Wheat Species Aegilops speltoides

Abstract: The inheritance of resistanee in the wild wheat species Ae. speltoides L. to Septoria glume blotch {Septoria nodorum Berk.) was investigated. It was characterized by two parameters measured on detached leaves, namely lesion size (LS) and length of latent period (LP), and by the severity of the disease under field conditions (DS). The genetic analysis was based on the P, and F2 generations of a 4 X 4 diallel cross between four Ae. speltoides accessions showing differential resistance to the pathogen. The three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
2
5
0
Order By: Relevance
“…A . similar "susceptible deviation" of F2 and F3 was observed in T. aestivum (ECKER et al 1989a), but with the Fj at the mid-parent point. In contrast, the additive-dominance model was found adequate for the control of glume blotch resistance in the species Ae, speltoides (ECKER et al 1989 b).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…A . similar "susceptible deviation" of F2 and F3 was observed in T. aestivum (ECKER et al 1989a), but with the Fj at the mid-parent point. In contrast, the additive-dominance model was found adequate for the control of glume blotch resistance in the species Ae, speltoides (ECKER et al 1989 b).…”
Section: Discussionsupporting
confidence: 73%
“…Sources of resistance to the disease were found in cultivated wheat (SCHAREN and EYAE 1980, NASS and JOHNSTON 1985, GRIFFITHS and JONES 1987, CUNEER et al 1988) and also in some of its wild relatives (SCOTT and BENEDIKZ 1980, SCOTT et al 1981, ToMEREiN et al 1984, ECKER et al 1989b. The resistance to Septoria glume blotch in the cultivated bread wheat {T. aestivum) is polygenica-Iy inherited (ROSIEELE and BROWN 1980, RAPIL-EY 1981, NEESON and GATES 1982, KARJAEAINEN 1983, ECKER et al 1989a). The nature and mode of inheritance of the resistance in the wild wheat species have not been reported so far.…”
mentioning
confidence: 99%
“…The reaction of F 1 plants and the segregation of F 2 and F 2:3 populations from the reciprocal crosses of 1644/1193 and 1193/1644 indicated that no maternal effects were involved in the inheritance of leaf rust and stem rust resistance (Tables 2 and 3). A similar result was reported by Ecker et al (2,3) in their study on the genetics of Septoria glume blotch resistance in the closely related species of A. speltoides and A. longissima. In contrast, marked differences were detected in the F 2 segregation ratio of reciprocal crosses between leaf rust resistant and susceptible A. speltoides accessions (E. Millet, unpublished data).…”
Section: Resultssupporting
confidence: 81%
“…This study was the first to characterize the genetics of disease resistance in A. sharonensis, and one of the few completed in any of the species of the section Sitopsis (2,3). Our results clearly demonstrated that resistance to wheat leaf rust, stem rust, and powdery mildew in A. sharonensis is controlled by dominant genes with major effect.…”
Section: Resultsmentioning
confidence: 52%
“…This is usually done using standard bi-parental crosses and molecular mapping to determine the number and chromosomal location of rust resistance genes (Ecker et al 1990;Yang et al 2003). An alternative means for mapping and tagging rust resistance genes that does not require bi-parental crosses is association mapping.…”
Section: Introductionmentioning
confidence: 99%